CHRONIC DIARRHEAS IN PEDIATRIC PRACTICE: MODERN APPROACH TO DIAGNOSTICS - I.N. Zaharova; Yu.A. Dmitrieva (Вопросы современной педиатрии, 2011)
(Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (6): 162–165)